Enhancing the Competitiveness of the Leather Industry in Egypt - Mostafa, Eman Mohamed Abdel-latif (The Arab Journal of Administration, 2025)
The leather industry is one of the most critical industries in Egypt, which is currently suffering from some deterioration that negatively affects its competitiveness. Hence, the problem of the study was that despite the availability of the necessary raw material for the leather industry in Egypt, which is a positive point in support of this industry to enhance its international position and competitiveness in global markets, this industry suffers from some problems and difficulties in addition to its low competitiveness. Then, the need arose to learn how to improve the competitiveness of this industry. During the study, the competitiveness of the leather industry was measured through several indicators, including the RCAI of Béla Balassa, the market share index, the value-added indicator, technology intensity use indicator, the development of average wages indicator, and the proportion of the primary raw materials involved in production (local and imported) indicator, as well as focusing on industrial clusters as one of the ways to enhance and support the competitiveness of the leather industry in Egypt. One of the essential results of the study is the small size of the market share of the leather sector in Egypt in the global commercial markets in general. However, the market share of raw and tanned leather was the highest compared to both leather products and leather shoes. In addition, Egypt enjoys a competitive advantage concerning raw and tanned leather. The RCAI values were more significant than a whole one, in addition to the escalating increase in imports of leather products during the period (2001-2019), which occupied the largest part of the total imports of the leather sector in Egypt during that period. The study concluded with several recommendations, including the need to disclose the obstacles facing leather companies in Egypt and setting a clear timetable to work on solving these obstacles, in addition to the need to provide the necessary support to organize specialized training courses in the field of the leather industry and tanning to provide technical cadres. Such technical cadres help improve product quality and increase productivity, as well as the need for government intervention to provide the whole production requirements for the leather sector at reasonable prices. This will help the industry to achieve high added value, and this reflects the competitive advantage of the sector, as well as the interest in the strategy of industrial clusters due to its importance and ability to contain the imbalance that the leather industry suffers from in Egypt, especially the industrial cluster in Al-Rubiki City and its potential capacity to export in the coming period.